Method for preparing perovskite solar cell with assistance of silane surfactant

By using silane-based surfactants to modify the electron transport layer and improve the perovskite layer, the Si-O-Si conductive network is formed, which solves the problem of defects and moisture erosion limitations of perovskite solar cells, and the effect of improving photoelectric conversion efficiency and stability is achieved.

CN119604157APending Publication Date: 2025-03-11HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311158215.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing perovskite solar cells based on CsPbI3 are limited by severe defects and moisture erosion in performance, resulting in insufficient phase stability and crystal quality, affecting the efficiency and stability of the device.

Method used

The electron transport layer was modified by silane-based surfactants 3-aminopropyltriethoxysilane (APTES) and 3-aminopropyltriethoxysilane (APTMS), and the perovskite layer were used to modify the electron transport layer, improve the film quality of the perovskite layer, and act as a perovskite passivation layer to form a Si-O-Si conductive network to prevent moisture erosion.

Benefits of technology

By improving the electron mobility of the electron transport layer, improving the morphology and crystal quality of the perovskite layer, and passivating the surface defects of the perovskite, the photoelectric conversion efficiency and stability of the perovskite solar cells are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604157A_ABST
    Figure CN119604157A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar cell materials and technologies, and particularly relates to a preparation method of a silane surfactant, a passivation modification layer and a perovskite solar cell. 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane is adopted to modify and improve the interface and internal structure of the perovskite solar cell, moisture in air reacts with silane and is hydrolyzed to form a Si-O-Si conductive network, carrier transport is promoted, uncoordinated lead ions and iodine vacancies of perovskite are passivated, internal defects of a thin film are reduced, and the performance of the thin film is improved. The water erosion is reduced, and the purpose of improving the device performance is achieved. The maximum efficiency of the prepared inorganic CsPbI3 perovskite solar cell can reach 20.50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cell materials and technologies, and in particular relates to a silane surfactant, a passivation modification layer and a preparation method of a perovskite solar cell. Background Art

[0002] As one of the applications of perovskites, metal halide perovskite solar cells have developed rapidly in the past decade and have been proven to be a photovoltaic technology with great commercial application potential. Although the photoelectric conversion efficiency of traditional organic-inorganic hybrid perovskite solar cells has exceeded 26.0%, which is comparable to that of silicon-based solar cells, volatile organic components will seriously affect the long-term stability of the device and hinder its commercial development. Therefore, replacing volatile organic components with inorganic cations is a way to solve this problem. In particular, Cs-based CsPbX 3 (X=I, Br) has attracted extensive attention due to its excellent water stability and thermal stability. 3 The band gap of CsPbI is about 2.3 eV, which is too large for photovoltaic applications and has insufficient light absorption capacity. 3 With a band gap of 1.73 eV, it is well suited for photovoltaic applications and is an ideal candidate for silicon tandem solar cells.

[0003] In the past few years, CsPbI 3 Perovskite solar cells have made amazing progress. Currently, CsPbI 3 The power conversion efficiency of solar cells has reached 21.8%, exceeding its Shockley-Queisser limit of 70%. 3 The tolerance coefficient is close to the limit of perovskite phase transition, and it is easy to transform from the black α phase to the non-photoactive yellow δ phase at room temperature. A research group reported that using DMAPbI 3 (or HPbI 3 ) intermediates to replace PbI 2 As a precursor, it can form a room temperature stable black γ phase, which not only significantly improves the phase stability but also reduces the defect density, thereby greatly improving the device performance. 3 The performance of perovskite solar cells is still largely limited by the non-radiative recombination caused by severe defects and the ubiquitous band mismatch between different functional layers. On this basis, in order to further improve the CsPbI 3 In order to improve the phase stability and crystal quality of perovskites, people have adopted a variety of strategies, including interface burial engineering, additive engineering, surface engineering, etc. Some theoretical studies have shown that from the perspective of formation energy, there are a large number of iodine vacancies (V i), which will lead to severe non-radiative recombination. These defects will eventually affect the efficiency and stability of the device, which shows the importance of defect management in inorganic perovskite solar cells. More importantly, moisture in the air penetrates the interface, corrodes the photoactive layer, and the black phase CsPbI 3 Easy to transform into yellow phase CsPbI 3 Therefore, passivating CsPbI 3 Thin film defects are one of the most effective and direct ways to improve device performance.

[0004] Surfactants are small amphiphilic molecules composed of hydrophobic and hydrophilic groups. They have unique surface tension and low surface energy, and have the driving force to migrate to the surface of perovskite. They have attracted great interest in recent years. In most surfactants, the hydrophobic functional group has a long chain that prevents the perovskite film from being eroded by water. Among them, the hydrophilic group such as -NH 2 , -SH, etc. can passivate uncoordinated Pb 2+ or with I - Form hydrogen bonds and enhance the interaction between perovskite crystals, thereby reducing defects inside and on the surface of the perovskite and reducing non-radiative recombination. Most traditional surfactants are insulating, resulting in blocked carrier transport and reduced short-circuit current in perovskite solar cell devices.

[0005] Silane surfactants such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane can hydrolyze with moisture in the air to form a Si-O-Si conductive network, enhance the transmission performance of perovskite solar cell devices, and prevent moisture erosion. They are excellent materials for optimizing perovskite films. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an electron transport layer, a method for preparing a perovskite layer, a method for preparing a perovskite passivation layer, a method for preparing a perovskite solar cell and the obtained solar cell.

[0007] The inventors of the present invention have found that silane surfactants can modify the electron transport layer to improve the electron mobility of the electron transport layer, can also be added as additives to the perovskite layer to improve the quality of the perovskite film, and can also be used as a perovskite passivation layer to passivate the surface defects of the perovskite and prevent water erosion, thereby improving the performance of the device. The names of the silane surfactants used in the present invention are: 3-aminopropyltriethoxysilane (APTES) and 3-aminopropyltrimethoxysilane (APTMS), and their chemical formulas are C 9 H 23 NO 3 Si, C 6 H 17 NO 3 Four.

[0008] The technical solution provided by the present invention is as follows:

[0009] The inventors of the present invention provide a method for preparing an electron transport layer, comprising the following steps:

[0010] An electron transport layer is prepared on a substrate, and then an isopropanol solution of APTES and APTMS with a concentration of 0.001-0.1 M is prepared, and the prepared electron transport layer is immersed in the APTES or APTMS solution for 30-120 minutes, and then annealed at 70-100° C. for 5-10 minutes to obtain the electron transport layer.

[0011] The inventors of the present invention have discovered that APTES and APTMS can be used as an interface layer to modify the electron transport layer and enhance the electron transport capability.

[0012] The inventors of the present invention provide a method for preparing a perovskite layer, comprising the following steps:

[0013] (1) In DMAPbI 3 Add 0.001M-0.1M APTES or APTMS to the DMF / DMSO solution of CsI, and heat and stir at 60-80°C until it becomes clear to obtain CsPbI 3 Precursor fluid.

[0014] (2) The CsPbI obtained in step 3 The precursor solution is spin-coated onto the modified electron transport layer, and then annealed in air at 170-210° C. for 10-30 min.

[0015] (3) Cooling to room temperature to obtain the perovskite layer.

[0016] The inventors of the present invention have found that APTES and APTMS as additives can significantly improve the morphology of perovskite thin films, increase the size of perovskite grains, and strengthen the interaction between lattices, thereby improving the performance of perovskite solar cells.

[0017] The present invention also provides a method for preparing a perovskite surface passivation layer, comprising the following steps:

[0018] A chloroform solution of APTES and APTMS with a concentration of 0.001-0.1 M is prepared and spin-coated on the perovskite layer, and then annealed at 75-85° C. for 4-6 minutes to obtain the perovskite passivation layer.

[0019] The inventors of the present invention have found that APTES and APTMS as passivation layers can significantly improve the morphology of perovskite thin films, form a dense Si-O-Si conductive network on the perovskite surface, enhance the transport of carriers, and passivate uncoordinated lead ions and iodine vacancies, thereby improving the performance of perovskite solar cells.

[0020] The present invention also provides a method for preparing a perovskite solar cell, comprising the following steps:

[0021] (1) Obtain a clean substrate;

[0022] (2) preparing an electron transport layer on the substrate obtained in step (1) by using the electron transport layer preparation method described above;

[0023] (3) preparing a perovskite layer on the electron transport layer obtained in step (2) by using the above-mentioned perovskite layer preparation method;

[0024] (4) preparing a perovskite passivation layer on the perovskite layer obtained in step (2) by using the above-mentioned perovskite surface passivation layer preparation method;

[0025] (5) preparing a hole transport layer on the perovskite passivation layer obtained in step (4);

[0026] (6) Preparing an electrode on the hole transport layer to obtain the perovskite solar cell.

[0027] Based on the above technical solution, it is possible to improve the carrier transmission capacity, reduce defects inside and on the surface of the perovskite layer, improve the photogenerated charge separation ability, and reduce the erosion of perovskite by moisture in the air, thereby improving the performance of perovskite solar cells.

[0028] Specific:

[0029] In step (1), the substrate is transparent conductive glass FTO;

[0030] In step (2), the electron transport layer is TiO 2 layer and an APTES or APTMS layer thereon;

[0031] In step (3), the perovskite layer is CsPbI doped with APTES or APTMS. 3 Perovskite layer;

[0032] In step (4), the perovskite passivation layer is an APTES or APTMS layer.

[0033] In step (5), the hole transport layer is a fully oxidized spiro-OMeTAD layer;

[0034] In step (6), the electrode is an Au electrode.

[0035] 0035. The present invention also provides a perovskite solar cell prepared by the above preparation method, characterized in that: its structure is FTO / TiO 2 +APTES / APTES-CsPbI 3 / APTES / spiro-OMeTAD / Au or FTO / TiO 2 +APTMS / APTMS-CsPbI 3 / APTMS / spiro-OMeTAD / Au.

[0036] 0036. Specifically, the concentration of APTES or APTMS is 0.001M-0.1M.

[0037] A specific preparation process of the present invention is as follows:

[0038] (1) Cleaning of fluorine-doped tin oxide FTO glass substrate: Use glass cleaning solution, deionized water, isopropanol, and ethanol to ultrasonically clean the FTO glass substrate for 30 minutes. Then take out the glass substrate and blow dry it with a nitrogen gun, and finally place it in a plasma cleaning machine and clean it with air for 5 minutes.

[0039] (2) Preparation of electron transport layer: The FTO glass substrate was immersed in a 200 mL aqueous solution containing 4.5 mL of titanium tetrachloride at 70 °C for 60 min, then rinsed with distilled water and annealed at 200 °C for 30 min to prepare TiO 2 layer.

[0040] (3) Preparation of perovskite solution and film: Weighing DMAPbI 3 and CsI (1M) crystal powder in a glass bottle, then add solvents DMF and DMSO in a volume ratio of 4:1, and stir at 70℃ for two hours until the solution becomes clear and transparent to obtain a precursor solution. Then take 60 µL of the precursor solution and drop it on the TiO 2 +APTES or TiO 2 +APTMS substrate, spin coating at 600 rpm for 6 seconds and 4000 rpm for 30 seconds, annealing at 180°C in air for 15 minutes, and naturally cooling to room temperature.

[0041] (4) Preparation of hole transport layer: First, weigh 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) powder into a glass bottle, then add 1 mL of chlorobenzene solvent, then add 17.5 µL of 520 mg / mL lithium salt acetonitrile solution and 28.8 µL of tetra-tert-butylpyridine, shake until fully dissolved, and the solution is bright yellow and transparent. Take an appropriate amount of solution and spread it evenly on the perovskite film, and complete the spin coating step with a spin coating time of 30 seconds, a rotation speed of 4000 rpm, and an acceleration of 2000 rpm / s. After all samples are completed, place the samples in a drying cabinet for at least 16 hours to allow spiro-OMeTAD to be fully oxidized.

[0042] (5) Preparation of metal electrodes: A 70 nm gold electrode was deposited onto the hole transport layer by thermal evaporation in a high vacuum environment to complete the device preparation. During the evaporation process, the first 10 nm of Au was slowly evaporated at a speed of 0.1 Å / s to reduce damage to the hole transport layer. The initial vacuum degree of evaporation was 5×10 -4 Pa.

[0043] The present invention has the following beneficial effects:

[0044] Using APTES and APTMS to modify the electron transport layer can effectively improve the electron transport capacity of the electron transport layer, reduce the series resistance of the device, and effectively improve the crystallization process of perovskite, increase the short-circuit current and fill factor of the device, thereby improving the photoelectric conversion efficiency of the device.

[0045] (2) The use of APTES and APTMS to dope the perovskite layer can significantly improve the morphology of the perovskite film, increase the size of the perovskite grains, strengthen the interaction between the lattices, reduce the defects of the perovskite film, obtain high-quality perovskite films, and improve the photoelectric conversion efficiency and stability of perovskite solar cell devices.

[0046] (3) APTES and APTMS are used as the perovskite surface passivation layer to passivate the uncoordinated lead ions and iodine vacancies on the perovskite surface. They can also react with moisture in the air to hydrolyze to form a Si-O-Si conductive network, thereby enhancing carrier transport, reducing moisture erosion, and improving the photoelectric conversion efficiency and stability of perovskite solar cell devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell prepared by the present invention.

[0048] Figure 2 It is the JV curve of the device obtained by modifying the electron transport layer with APTES or APTMS.

[0049] Figure 3 It is the JV curve of the device obtained by doping the perovskite layer with APTES or APTMS.

[0050] Figure 4 It is the JV curve of the device obtained by passivating the perovskite layer with APTES or APTMS.

[0051] Figure 5 This is a scanning electron microscope (SEM) image of the perovskite film of the control group.

[0052] Figure 6 is a scanning electron microscope (SEM) image of the APTES-treated perovskite film.

[0053] Figure 7 is a scanning electron microscope (SEM) image of the APTMS-treated perovskite film. Implementation

[0054] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0055] Example 1

[0056] The control group is a device that is not modified with APTES or APTMS, and the preparation method is the above device preparation process. Experimental group 1 uses APTES to modify the electron transport layer. The specific process is: prepare an APTES isopropanol solution with a concentration of 0.01M as the modification solution of the electron transport layer, deposit TiO 2 The FTO glass substrate with a layer of 2 was immersed in the solution for 2 hours, dried with nitrogen, and annealed at 80 degrees Celsius for 5 minutes. Then the perovskite layer and the hole transport layer were spin-coated, and the Au electrode was evaporated to complete the device preparation.

[0057] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 2 As shown in Figure 2, the base efficiency reached 16.82%, and the device with APTES modified electron transport layer reached the highest efficiency of 17.70%, the open circuit voltage was 1.17 V, and the current density was 18.98 mA / cm 2 , the filling factor is 79.8%.

[0058] Example 2

[0059] The control group is a device that is not modified with APTES or APTMS, and the preparation method is the above device preparation process. Experimental group 2 uses APTMS to modify the electron transport layer. The specific process is: prepare an APTEMS isopropanol solution with a concentration of 0.01M as the modification solution of the electron transport layer, deposit TiO2 The FTO glass substrate with a layer of 2 was immersed in the solution for 2 hours, dried with nitrogen, and annealed at 80 degrees Celsius for 5 minutes. Then the perovskite layer and the hole transport layer were spin-coated, and the Au electrode was evaporated to complete the device preparation.

[0060] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 2 As shown in Figure 2, the base efficiency reached 16.82%, and the device with APTES modified electron transport layer reached the highest efficiency of 17.67%, the open circuit voltage was 1.15 V, and the current density was 19.66 mA / cm 2 , the filling factor is 78.0%.

[0061] Example 3

[0062] The control group was a device without APTES or APTMS added, and the preparation method was the above device preparation process. Experimental group 3 added APTES to the perovskite layer. The specific process was as follows: prepare the electron transport layer, prepare APTES with a concentration of 0.01M and DMF / DMSO mixed solution as the perovskite precursor solvent, and add DMAPbI 3 The precursor solution of perovskite was prepared by dissolving CsI in a mixed solvent at a molar ratio of 1:1. The perovskite layer and hole transport layer were then spin-coated, and the Au electrode was evaporated to complete the device preparation.

[0063] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 3 As shown in Figure 2, the base efficiency reached 16.75%, and the device with APTES-added perovskite reached a maximum efficiency of 17.26%, an open circuit voltage of 1.15 V, and a current density of 18.98 mA / cm 2 , the filling factor is 79.1%.

[0064] Example 4

[0065] The control group was a device without adding APTES or APTMS, and the preparation method was the above device preparation process. Experimental group 4 added APTMS to the perovskite layer. The specific process was as follows: prepare the electron transport layer, prepare APTMS with a concentration of 0.01M and DMF / DMSO mixed solution as the perovskite precursor solvent, and add DMAPbI 3 The precursor solution of perovskite was prepared by dissolving CsI in a mixed solvent at a molar ratio of 1:1. The perovskite layer and hole transport layer were then spin-coated, and the Au electrode was evaporated to complete the device preparation.

[0066] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 3As shown in Figure 2, the base efficiency reached 16.75%, and the device with APTMS-added perovskite reached the highest efficiency of 16.93%, the open circuit voltage was 1.16 V, and the current density was 19.23 mA / cm 2 , the filling factor is 76.1%.

[0067] Example 5

[0068] The control group is a device that is not modified with APTES or APTMS, and the preparation method is the above-mentioned device preparation process. Experimental group 5 uses APTES to modify the surface of the perovskite layer. The specific process is: prepare the electron transport layer and spin-coat the perovskite layer. A 0.01M APTES chloroform solution is prepared as the modification solution of the perovskite layer, spin-coat the solution, and anneal at 80°C for 5 minutes. Then spin-coat the hole transport layer and evaporate the Au electrode to complete the device preparation.

[0069] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 4 As shown in Figure 2, the base efficiency reached 16.82%, and the device with APTES modified perovskite layer surface reached the highest efficiency of 19.02%, the open circuit voltage was 1.17 V, and the current density was 20.01 mA / cm 2 , the filling factor is 80.9%.

[0070] Example 6

[0071] The control group is a device that is not modified with APTES or APTMS, and the preparation method is the above-mentioned device preparation process. Experimental group 6 uses APTMS to modify the surface of the perovskite layer. The specific process is: prepare the electron transport layer and spin-coat the perovskite layer. A 0.01M APTMS chloroform solution is prepared as the modification solution of the perovskite layer, spin-coat the solution, and anneal at 80°C for 5 minutes. Then spin-coat the hole transport layer and evaporate the Au electrode to complete the device preparation.

[0072] The device is tested for its photoelectric performance, and the current-voltage (JV) test results are as follows: Figure 4 As shown in Figure 2, the basic efficiency reached 16.82%, and the device with APTMS modified perovskite layer surface reached the highest efficiency of 18.04%, the open circuit voltage was 1.16V, and the current density was 19.45mA / cm 2 , the filling factor is 79.5%.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing perovskite solar cells with the assistance of silane surfactants, characterized in that: The method includes introducing silane surfactants such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane into the surface of the perovskite light-absorbing layer in the perovskite solar cell, into the CsPbI3 precursor solution of the light-absorbing layer, and at the interface between the electron transport layer and the perovskite light-absorbing layer.

2. The method for introducing a silane surfactant into a perovskite solar cell according to claim 1, characterized in that: The lead-based material of the perovskite light-absorbing layer includes one or more of DMAPbI3, Pb(CH3COO)2, and PbBr2; the perovskite light-absorbing layer also includes one or more of CsI, CsBr, and CsCl.

3. The method for introducing a silane surfactant into a perovskite solar cell according to claim 1, characterized in that: 3-Aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane can react with moisture in the air to self-assemble to form a Si-O-Si conductive network.